The Problematics of conditional release decisions in law enforcement for corruption crimes in Indonesia - Rufinus Hotmaulana Hutauruk; Emiliya Febriyani; Muhammad Faiz (Journal of Law Science, 2024)
The granting of conditional release decisions to prisoners with corruption cases who have fulfilled the conditions for release from the sentence period in Indonesia has become a controversial event that is considered by the public in general. The granting of parole can make it easier for prisoners to be free without having to serve the full legal period imposed by the judge. This can actually be very detrimental to the state in various sectors such as the economy, education, investment, industry, finance and others. Especially if the perpetrator of corruption is a state official who is authorized to maintain welfare and legal justice in the community. The status and position of a perpetrator will be of concern to many people, especially in granting conditional release in Indonesia. This research is a normative juridical research with a statutory approach and conceptual approach. From the results of the research it is obtained that in order to grant the rights of prisoners, namely conditional release decisions, especially for corruptors, it must be accompanied by supervision from all levels and accompanied by careful consideration so as not to injure the principles of justice, certainty and usefulness in society.